2017
DOI: 10.1007/s10147-017-1229-4
|View full text |Cite
|
Sign up to set email alerts
|

Goshajinkigan for reducing chemotherapy-induced peripheral neuropathy: a systematic review and meta-analysis

Abstract: Goshajinkigan tended to prevent persistence but not severity of CIPN. Higher quality trials using multiple measures are needed in the future to clarify the preventive effect of Goshajinkigan and to assess the various aspects of CIPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Consistently, in 2017, Kuriyama et al conduct a systematic review and meta-analysis, and further demonstrate that Goshajinkigan is impossible to prevent peripheral neuropathy in patients receiving neurotoxic chemotherapy. Next, Hoshino et al also conduct a systematic review and show that Goshajinkigan tends to prevent persistence but not severity of chemotherapy-induced peripheral neuropathy (Hoshino et al, 2018 ). Given the low quality and insufficient amount of the evidence, use of Goshajinkigan as standard of care is not currently recommended (Kuriyama and Endo, 2018 ).…”
Section: Need To Clarify the Prevention Of Neurotoxicitymentioning
confidence: 99%
“…Consistently, in 2017, Kuriyama et al conduct a systematic review and meta-analysis, and further demonstrate that Goshajinkigan is impossible to prevent peripheral neuropathy in patients receiving neurotoxic chemotherapy. Next, Hoshino et al also conduct a systematic review and show that Goshajinkigan tends to prevent persistence but not severity of chemotherapy-induced peripheral neuropathy (Hoshino et al, 2018 ). Given the low quality and insufficient amount of the evidence, use of Goshajinkigan as standard of care is not currently recommended (Kuriyama and Endo, 2018 ).…”
Section: Need To Clarify the Prevention Of Neurotoxicitymentioning
confidence: 99%
“…GJG significantly decreased glycated hemoglobin and progression of neuropathy (ankle reflex) when compared with the control. GJG is also used to prevent and relieve peripheral neuropathy due to chemotherapy (115).…”
Section: Neuropathic Painmentioning
confidence: 99%
“…Another 3 studies focused on oxaliplatin (evidence of low quality). In terms of the incidence of grade ≥2 OIPN, Tian et al 23 37,38 Incidence of Grade ≥3 CIPN/OIPN. A total of 7 studies summarized evidence on this outcome (evidence of low quality).…”
Section: Quality Of Evidence In the Included Systematic Reviews Assesmentioning
confidence: 99%
“…Two studies reported on safety outcomes with regard to incidence of adverse events and hematological toxicities. 29,37 One also reported on the rate of response to chemotherapy. Hoshino et al 37 , but there was no statistically significant difference in severe thrombocytopenia and severe kidney injury.…”
Section: Quality Of Evidence In the Included Systematic Reviews Assesmentioning
confidence: 99%
See 1 more Smart Citation